Tanggung Jawab Pengguna dan Pemilik Kendaraan dalam Sewa-Menyewa Kendaraan Mobil B354 Rent Car di Kecamatan Kelapa Lima Kota Kupang - Susan Marokana Naomi Kapitan; Orpa Julian A. Nubatonis; Yossie Maria Y. Jacob (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
This study aims to analyze the responsibilities of users and vehicle owners in the lease of B354 Rent Car vehicles in Kelapa Lima District, Kupang City. This type of research is empirical juridical research, primary data obtained by interview with 8 respondents and supported by secondary data, qualitative descriptive data analysis. The results of this study indicate that in its implementation the responsibilities that occur at B354 Rent Car are still not in accordance with what the rights and obligations of each party are contained in a mutual agreement in an agreement made orally or in writing, there is still negligence from the renter which results in non-achievement of achievements in the agreement that has been made together. Factors inhibiting the implementation of the rental agreement from the rental party do not carry out the agreement in writing with all parties who rent properly because the procedure for implementing the agreement is too complicated and takes a long time and the ignorance of the tenants with the agreement and the importance of the agreement is made and the weakness of the existing rules. Tenants and business actors must be educated about rental procedures, especially car leases and there must be special attention from the government to business actors and the public regarding the rules and procedures for implementing agreements in leases and the importance of written agreements.